2023
DOI: 10.3389/fnagi.2023.1068316
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive impairment on the multi-scale dynamics of standing postural control during visual-search in older men

Abstract: BackgroundCognitive impairment disrupts postural control, particularly when standing while performing an unrelated cognitive task (i.e., dual-tasking). The temporal dynamics of standing postural sway are “complex,” and such complexity may reflect the capacity of the postural control system to adapt to task demands. We aimed to characterize the impact of cognitive impairment on such sway complexity in older adults.MethodsForty-nine older adult males (Alzheimer’s disease (AD): n = 21; mild cognitive impairment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A correlation has also been noted between standing postural balance and cognitive dysfunction, implying a link between balance maintenance and cognitive health 54 . Given that standing postural control often involves multitasking (e.g., reading or talking while standing), it could adversely affect cognitive task performance, especially in individuals with cognitive impairment 55 . Thus, the influence of posture on cognitive performance may depend on specific cognitive tasks, individual differences, and other factors.…”
Section: Standing Play Enhances Esports Performancementioning
confidence: 99%
“…A correlation has also been noted between standing postural balance and cognitive dysfunction, implying a link between balance maintenance and cognitive health 54 . Given that standing postural control often involves multitasking (e.g., reading or talking while standing), it could adversely affect cognitive task performance, especially in individuals with cognitive impairment 55 . Thus, the influence of posture on cognitive performance may depend on specific cognitive tasks, individual differences, and other factors.…”
Section: Standing Play Enhances Esports Performancementioning
confidence: 99%
“…A correlation has also been noted between standing postural balance and cognitive dysfunction, implying a link between balance maintenance and cognitive health (49). Given that standing postural control often involves multitasking (e.g., reading or talking while standing), it could adversely affect cognitive task performance, especially in individuals with cognitive impairment (50). Thus, the influence of posture on cognitive performance may depend on specific cognitive tasks, individual differences, and other factors.…”
Section: Standing Play Enhances Esports Performancementioning
confidence: 99%
“…If the attentional demands are greater than the capacity of an individual, dual tasking results in cognitive-motor interference, such that there is deterioration of performance on either or both tasks ( 12 , 13 ). Previous studies have shown that older adults with mild cognitive impairment (OAwMCI) experience higher cognitive-motor interference than cognitively intact older adults (CIOA) during volitional balance control tasks, resulting in increased standing postural sway and reduced gait speed while performing a cognitive task (e.g., visual search, digit span recall, word recall) ( 14 17 ). However, activities of daily living do not only involve gait and working memory tasks, but also entail the ability to recover from unpredictable balance threats induced by the environment (i.e., reactive balance control) ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%